2018
DOI: 10.1038/s41598-018-33257-6
|View full text |Cite
|
Sign up to set email alerts
|

Inactive matrix Gla protein is a novel circulating biomarker predicting retinal arteriolar narrowing in humans

Abstract: Active matrix Gla protein (MGP), a potent inhibitor of calcification in large arteries, protects against macrovascular complications. Recent studies suggested that active MGP helps maintaining the integrity of the renal and myocardial microcirculation, but its role in preserving the retinal microcirculation remains unknown. In 935 randomly recruited Flemish participants (mean age, 40.9 years; 50.3% women), we measured plasma desphospho-uncarboxylated MGP (dp–ucMGP), a marker of poor vitamin K status using an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
(81 reference statements)
2
17
0
Order By: Relevance
“…As observed by others, dp-ucMGP is associated negatively with eGFR estimated by MDRD and with albuminuria (S1 Table) [39,40]. However we don't find any association between dp-ucMGP and retinopathy treated by laser (S1 Table) despite some data suggesting that dp-ucMGP could be a marker of retinal health [42]. Additional studies are needed to explore specifically these associations in patients with diabetes.…”
Section: Discussionsupporting
confidence: 46%
“…As observed by others, dp-ucMGP is associated negatively with eGFR estimated by MDRD and with albuminuria (S1 Table) [39,40]. However we don't find any association between dp-ucMGP and retinopathy treated by laser (S1 Table) despite some data suggesting that dp-ucMGP could be a marker of retinal health [42]. Additional studies are needed to explore specifically these associations in patients with diabetes.…”
Section: Discussionsupporting
confidence: 46%
“…Basic and clinical studies have demonstrated the importance of appropriate vitamin K status for the health of the vascular system 23 and musculoskeletal tissues. 24 A recent study showed that circulating inactive dp-ucMGP is a long-term predictor of smaller retinal arteriolar diameter in the general population, 15 which highlights the potential role of vitamin K in retinal health. In the present study, dietary VitK1 supplementation can partially protect the apoptosis of RGCs from COH, which further confirmed the neuroprotective role of vitamin K. The beneficial effect of VitK1 may act through its antioxidative and anti-inflammatory effect, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…14 A recent study demonstrated that circulating dp-ucMGP (an inactive form of MGP protein that indirectly reflects the low vitamin K status) is a long-term predictor of smaller retinal arteriolar diameter in the general population, which highlights the potential beneficial effect of vitamin K supplementation in retinal health. 15 However, the pathophysiologic relationship between vitamin K and the optic neuropathy in glaucoma remains largely unknown.…”
mentioning
confidence: 99%
“…With high binding affinity to hydroxyapatite crystals, it is considered as one of the most important biological agents in the prevention of vascular calcification[ 11 - 13 ]. Furthermore, increased levels of its inactive dephosphorylated and uncarboxylated form, designated as dp-ucMGP, have been associated with number of different cardiovascular consequences and complications, including endothelial dysfunction, retinal arteriolar narrowing, atherosclerosis, increased aortic stiffness, and higher overall cardiovascular, non-cancer and total mortality[ 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%